Factors Impacting Quality of Life in a Group of Iranian Patients in Chronic Oral Mucosal Disease Following Treatment? - Mohammad Shooriabi; Sedigheh Modarres Mousavy; Farideh Kaabomeir; Elham Jafari (Wiley, 2024)
ABSTRACT Objective The objective of this study was to investigate the impact of treatment on the quality of life of patients with chronic oral mucosal diseases. Specifically, the study aimed to determine how treatment affects the changes in the quality of life of these patients. Methods This descriptive study involved 220 patients diagnosed with chronic oral mucosal lesions. Data were collected using the Chronic Oral Mucosal Disease Questionnaire, validated for use in Persian/Farsi. The study population was selected through convenience sampling. Data analysis employed descriptive statistical methods, including frequency and percentage distribution tables, graphs, measures of central tendency, and dispersion. Additionally, confidence intervals were utilized for the studied ratios and indices. Results Among the study population, 129 (58.6%) were male and 91 (41.4%) were female. The mean quality of life, as assessed by the utilized questionnaire, was 61.9 ± 13.2. The results indicated that females and unemployed individuals reported lower quality of life compared to males and employed individuals, respectively, with a statistically significant difference (p < 0.05). Conclusion In the population studied the quality of life of patients with chronic mucous membrane diseases was influenced by various factors, including gender, income, employment, and place of residence.